Modern Treatment of Patients with Purular Necrotic Forms of Diabetic Foot Syndrome (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
Diabetes mellitus (DM) is one of the most common diseases of our time. Type 2 diabetes (T2DM) occurs in 2–6% of the adult population and reaches the figure of about 120 million people. According to forecasts by WHO experts, by 2025 the number of patients with type 2 diabetes will be over 250 million people. Epidemiological studies claim that the true number of patients with this pathology is 2-3 times more than officially registered at the dispensary. This is due to the fact that diabetes of the first type (T1DM) is a congenital disease and the diagnosis is verified with the patronage and the preserved standards of professional examinations in childhood; while T2DM occurs in adulthood in the absence of proper attention to the first signs of the disease and does not attract attention until complications develop. Statistical studies prove that in patients with type 2 diabetes, atherosclerotic lesions of the main arteries are found several times more often than in people of the same age who do not suffer from type 2 diabetes. The treatment of diabetic micro- and atherosclerotic macroangiopathies and their complications occupies an important place in the everyday practical work of both surgeons and endocrinologists.